Pediatric Trauma Experience in a Combat Support Hospital in Eastern Afghanistan over 10 Months, 2010 to 2011. Issue 3 (March 2013) - Wilson, Kenneth L.; Schenarts, Paul J.; Bacchetta, Matthew D.; Rai, Pradeep R.; Nakayama, Don K.
We reviewed the pediatric trauma experience of one Combat Support Hospital (CSH) in Afghanistan to focus on injuries, surgery, and outcomes in a war zone. We conducted a review of all pediatric patients over 10 months in an eastern Afghanistan CSH. We studied 41 children (1 to 18 years; mean, 8.5 years; median, 9 years), 28 (68.2%) with penetrating injuries. Blasts (13 patients) and burns (nine) were the most common mechanisms. At arrival 19 (46.3%) underwent endotracheal intubation, four (9.8%) had no palpable blood pressure, 10.6 per cent (four of 38) a Glasgow Coma Score of 5 or less, 30.6 per cent (11 of 36) base deficits of 6 or less, and 41.7 per cent (15 of 36) hematocrit 30 or less. Red cells were given in 14 (34.1%) and plasma in 11 (26.8%). Of 32 total nonburn patients, 12 (37.5%) had multiple system injuries. Three-fourths of injuries were severe (75.8% [47 of 62] Abbreviated Injury Score 3 or greater). Thirty-two patients (78.0%) required major operations: burn and wound care, orthopedic, chest, abdominal, vascular, and neurosurgical. Second operations were performed in 16 (39.0%), most often burn and orthopedic procedures. Six died (14.6%), 13 were transferred to other hospitals (31.7%), and 20 were discharged to home (48.8%; two not noted). Broad experience in operative trauma care, pediatric resuscitation, and critical care is a priority for military surgeons.